State feedback impulsive control of computer worm and virus with saturated incidence - Meng Zhang; Kaiyuan Liu; Lansun Chen; Zeyu Li (Mathematical Biosciences and Engineering)
A state feedback impulsive model is set up to discuss the spreading and control of the computer worm and virus. Considering the transmission features, saturated infectious is adopted to describe the spreading in the model, and all the treatment measures, such as patching operating system and updating antivirus software, are assumed to take effect instantly. Then the model is analyzed with a novel method, and the existence and stability of order-1 limit cycle are discussed. Finally, the numerical simulation is listed to verify the result of the paper.